Temporal Incidence of Eriophyid Mites on Rose Rosette Disease-Symptomatic and -Asymptomatic Roses in Central Georgia, USA - Alejandra Monterrosa; Mathews L. Paret; Ronald Ochoa; Andrew Ulsamer; Shimat V. Joseph (Pathogens, 2022)
Phyllocoptes fructiphilus Keifer (Acari: Eriophyidae) is the vector of rose rosette virus (RRV), which causes rose rosette disease (RRD) in North America. The RRD symptoms, such as witches’ broom, flower, and leaf deformation, disrupt the aesthetic appearance of plants and cause plant mortality. Because there is no cure for RRV, it is critical to manage the vector and reduce the spread of the virus. The information on the phenology of P. fructiphilus on rose plants is essential to develop management strategies and reduce its spread. Thus, the objectives of the study were to determine 1) the phenology of eriophyid mites (including P. fructiphilus) in central Georgia due to its widespread occurrence in the state and 2) the incidence of eriophyid mites on closed and opened flower buds and other plant parts. In central Georgia, eriophyid mites, including P. fructiphilus were active on both symptomatic and asymptomatic plants from April to December. The mite densities were greater during July and August than during the remaining months on asymptomatic plants. The mites were more abundant on the RRD-symptomatic than on the asymptomatic plants. Similar numbers of eriophyid mites were observed on closed and opened flower buds. Eriophyid mite densities were greater on sepals and leaf bases than on other plant parts.